1995
DOI: 10.1007/bf00290726
|View full text |Cite
|
Sign up to set email alerts
|

The C-terminal domain of SIN1 in yeast interacts with a protein that binds the URS1 region of the yeast HO gene

Abstract: A protein or protein complex has previously been identified in Saccharomyces cerevisiae which both binds a short DNA sequence in URS1 of HO and interacts with SIN1. SIN1, which has some sequence similarity to mammalian HMG1, is an abundant chromatin protein in yeast and is thought to participate in the transcriptional repression of a specific family of genes. SIN1 binds DNA weakly, though it has no DNA binding specificity. Here we address the nature of the interaction between SIN1 and the specific DNA binding … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
13
0

Year Published

1995
1995
2006
2006

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 20 publications
0
13
0
Order By: Relevance
“…1). It was shown that one of these domains (amino acids 100 -162) was able to bind double-stranded DNA without substantial sequence specificity (6,11). Some key features of HMG boxes, however, were not present in this sequence, and its similarity to HMG was disputed (12).…”
mentioning
confidence: 99%
“…1). It was shown that one of these domains (amino acids 100 -162) was able to bind double-stranded DNA without substantial sequence specificity (6,11). Some key features of HMG boxes, however, were not present in this sequence, and its similarity to HMG was disputed (12).…”
mentioning
confidence: 99%
“…We have shown previously that the XBS can bind a protein that interacts with the C-terminal of SIN I [8]. A bacterially produced mutant sin 1-2 protein containing a single amino acid difference from the wild type SIN I was able to remove this protein from the XBS [4].…”
Section: Events At Tke )Ibs Cause the Overexpression Of Ho In Sin12 mentioning
confidence: 95%
“…HO) while it has not been shown to bind DNA in a sequencespecific manner. Previously we showed that the C-terminal of SIN I is able to contact a protein that does specifically bind a short DNA sequence (XBS) in the HO promoter [8]. In this paper we have further pursued the role of this DNA sequence in regulating the transcription of HO, and have shown that the HMGI domain of SINI itself can preferentially bind this sequence, These experiments have demonstrated that the XBS is an important component of the c;sregulatory sequences that participate in the modulation of HO transcription, and that this modulation is accomplished by interactions of SIN i and the SWI/SNF complex at this locus.…”
Section: C~hslommentioning
confidence: 99%
“…Several hypothetical functional domains in Sin1p have been defined based on genetic, structural, and biochemical considerations (6,9,21,(23)(24)(25). These domains include two HMG1-like domains, (amino acids 26-88 and 98-159), an acidic domain (amino acids 224-304), and a basic C-terminal domain (amino acids 303-333).…”
Section: Sin1p Binds Downstream Of Many Genes Just Upstream Of a Majormentioning
confidence: 99%